A Bhagavad Gita Lens on Building Ethical AI for Business - Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2026)
Background: The unprecedented integration of Artificial Intelligence into world business practice has raised unprecedented ethical and strategic dilemmas. Meanwhile, wisdom traditions emanating from ancient times, such as the Bhagavad Gita, have long stood to inform conceptualizations of duty, action, and consciousness. Today, these two worlds-modern technological strategies and ancient philosophical wisdom-remain separated by strict silos, with business often opting for efficiency over ethical reflection. Objectives: The review article is guided by three objectives: first, to explain the key philosophical concepts of the Bhagavad Gita-namely, dharma, karma, nishkama karma, atman, and gunas-in an easy-to-understand manner; second, to demarcate the current landscape of AI in businesses, focusing on its functional use in practice and the ongoing ethical issues it poses, including bias, accountability, and the future of work; and third, to build a useful, cross-disciplinary bridge by applying the conceptual framework of the Gita to diagnose and find solutions for these contemporary business problems. Methods: Focusing on the narrative review approach, this article intends to bring together primary sources on Hindu philosophy itself—in the form of translations and commentaries on the Bhagavad Gita—and present the findings in terms of business and technology literature using the comparative approach to these issues. Analysis: The analysis reflects strong affordances between the principles gleaned from the Gita and those applicable in AI ethics. The construct of Dharma contests the conventional corporate interest in profit maximization, instead pressing the value of purpose-driven design. Nishkama has implications in negating the commonplace approach of ‘move fast break things,’ pressing the importance of process rather than outcome. The construct of Atman serves to underscore the interlocutor in human-AI relationships, avoiding anthropomorphism with machines while making them responsible. The framework through three gunas (sattva, Rajas, Tamas) serves as an innovative system through framing the value of whether an AI is beneficial, exploitative, or even harmful in nature. Conclusion: This article finally argues that the Bhagavad Gita delivers to the age of AI in business an indispensable ethical tool kit. It also moves away from theoretical ethical concerns to propose the development of "Gita-inspired leadership" as well as very simple ethical checklists in business strategies. The final choice for businesses will not concern embracing or avoiding the development of AI; they will instead have to make choices in wisdom and duty or in shortsightedness and greed. Novelty: This study represents a pioneering effort as it engages the particular philosophic structure represented within the Bhagavad Gita, a non-Western approach to collective knowledge or wisdom, with the relevant considerations of artificial intelligence in business. Indeed, there are a great many studies calling for ethics in general.